The mediating role of resilience between perceived social support and sense of security in medical staff following the COVID-19 pandemic: A cross-sectional study - He, Qingxia; Xu, Peng; Wang, Huajun; Wang, Shibin; Yang, Lulu; Ba, Zhiqiong; Huang, Huigen (Frontiers in Psychiatry, 2023)
Background: The the coronavirus disease 2019 is not only a serious threat to public life and health, but also has a serious impact on people's mental health, especially that of medical staff. Perceived social support is an importance factor in sense of security. Objective: To explore the potential mediating role of resilience in the association between perceived social support and the sense of security among Chinese medical staff following the COVID-19 pandemic. Methods: The multi-stage proportionally stratified convenience sampling method was adopted to select 4,076 medical staffs from 29 hospitals in Guangdong province between September 2020 and October 2020. The Sense of Security Scale for Medical Staff, Chinese version of Connor-Davidson Resilience Scale and Perceived Social Support Scale were employed in this study. SPSS 23.0 and AMOS24.0 software were used for statistical analysis and structural equation modeling (SEM). Regression analysis was used to select the control variables to be included in the SEM. SEM analysis was conducted to verify the mediating effect of resilience on the relationship between perceived social support and a sense of security. Results:Pearson's correlations analysis showed that perceived social support and resilience were positively associated with sense of security (correlation coefficients range from 0.350 to 0.607, P < 0.01), and perceived social support (correlation coefficients range from 0.398 to 0.589, P < 0.01) was positively associated with resilience. Structural equation modeling revealed that resilience played a partial mediating role in the association between perceived social support and sense of security (60.3% of the effect of perceived social support on security was direct effect, and 39.7% of the effect was mediated by resilience). Conclusions: Hospital managers should make efforts to develop the resilience. Interventions based on resilience to enhance the perceived social support and to strengthen the sense of security should be developed.